Livre iniciativa e limites à regulação estatal na perspectiva do Supremo Tribunal Federal - Possamai, Giancarlo Bernardi (2014)
Even though the Federal Constitution establishes as a rule that economic relations are structured over free enterprise, which is one of the economic order fundamentals, a few other constitutional principles seem to have an antagonistic meaning towards this liberty, and the ambiguities that are thus entailed cannot be ignored. Therefore, the present dissertation aims precisely to analyze the Brazilian Supreme Court approach on state regulation conditioning private actors in their economic activities, investigating if it is possible to note an evolution in the way the Court deals with the issues that are put before it, as well as verify how the different interests that come up in practice are balanced. In that respect, the work concludes that the Court, based in a very superficial argumentation, tends to defend the state acts that are submitted to its review. Yet, despite the transformations that the society and the State have gone through in the last twenty years, it is not possible to note a significant change in the Court s understanding, once it is still attached to traditional ideas that affirm the almost absolute prevalence of the public sector over the private one